The features of primary seed production of winter bread wheat - Yu. G. Skvortsova; Т. I. Firsova; N. G. Chertkova; G. A. Filenko (Зерновое хозяйство России, 2020)
The current paper has presented the features of primary seed production of winter bread wheat in the Rostov region and highlighted the main methods of varietal renewal, which make it possible to obtain high-quality seed material with strict preservation of their purity, biological and productive traits, in the amounts that meet the needs of the farms. The purpose of the research was to organize primary seed production of new and commercial varieties of winter bread wheat, which allows maintaining varietal purity and providing the required number of seeds of higher reproductions. There have been conducted the field trials to identify the best indicators of seed productivity, varietal and sowing qualities in the primary links of seed production. Seed production is based on individual-family selection with a two-year assessment of the progeny. The main percentage of variety rejection in the laboratory conditions was made according to such indicators as 1000 seed weight, family productivity, uniformity and plump condition of kernels within the family. In PIP-1 the rejection among the varieties ‘Volnitsa', ‘Volny Don', ‘Zhavoronok', ‘Polina', ‘Ambar', ‘Donskaya Stepp', ‘Yubiley Dona' was carried out for all indicators from 16 to 32%. The variety ‘Zhavoronok' was found the best according to the indicators and its rejection rate was 7%. In PIP-2 over the years of variety trials, the studied varieties of winter bread wheat were rejected in the field for all indicators from 2 to 7%. In the laboratory conditions, the rejection rate was slightly different and ranged from 1 to 8%. The highest seed productivity was formed by the varieties ‘Zernogradka 11' (11.2 t/ha), ‘Ermak' (10.8 t/ha), ‘Marafon' (11.5 t/ha) and ‘Krasa Dona' (11.5 t/ha). The percentage of seed productivity of the studied varieties varied from 67.4% to 93.3%. The maximum 1000 seed weight was identified in the varieties ‘Krasa Dona' (52.7 g), ‘Volny Don' (49.8 g), ‘Volnitsa' (49.1 g). The indicators of the main varietal and sowing qualities of winter wheat seeds corresponded to GOST R 52325-2005.